Sliding Mode controlled PV-Fed-Fly Back-Converter-System with Enhanced Dynamic Response - A.Wisemin Lins , R.Krishnakumar (International Journal of Advanced Science and Technology, 2020)
Power Quality improvement utilizing PV-based fly back-system is a trustworthy technique. Battery and PV-sources are considered as an input. This work deals with Slide Mode controlled PV-fed-Flyback-converter-system (FBCS). Sliding mode controller remains insensitive to the external disturbances and the uncertain parameter variations. Sliding mode controller is a two loop controller. The inner current loop and the outer voltage loop controller improves the response of the controller. MATLAB - Simulink model for FBCS is established utilizing the fundamentals of Simulink and cascaded-loop examinations are implemented with PI and the sliding mode-Controller. The results shows improved dynamic performance in terms of rise time, settling time and steady state error